Alih Aksara Teks Manuskrip Salinan Haji Sulaiman; Pahala Membaca dan Makna Huruf Fatihah - Suryan Masrin; Saiful Anwar (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2021)
This article aims to present a manuscript transliteration of a copy of Haji Sulaiman which explains the Reward of Reading and the Meaning of the Fatihah Letter. The result of this research is to present a text that can be read and understood by the public at this time in the manuscript text of Haji Sulaiman's copy which explains about the reward of reading and the meaning of fatihah letters (PM2HF). This manuscript tells the reward of reading Fatihah in the five daily prayers, the names of Fatihah, the seven letters that are not allowed in reading Fatihah, the meaning of letters in Fatihah, including the hijaiyah letters (called prayer alif 30), and means by verse Fatihah. In the Reading Pahala Manuscript and the Meaning of the Fatihah Letters, a copy of Haji Sulaiman, the text is a vocabulary that shows the variety of ancient Malay in it.